Pengendalian Infestasi Fascioliasis Ternak Sapi Rakyat Melalui Pemeriksaan dan Pengobatan di Desa Ngentakrejo, Kulon Progo - M. Mukhlis Aditya Pangestu; Meiandra Ragil Pinesthy; Vidya Maharani; Maria Advensia Eka Setyaningrum; Fajar Budi Lestari; Suryanto Suryanto; Clara Ajeng Artdita (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Livestock health status in the traditional farming system of Ngudi Rahayu Farmer Group, Ngentakrejo Village, Lendah Subdistrict, Kulon Progo Regency, Yogyakarta continues to face challenges due to fascioliasis. This community service program aimed to identify the fascioliasis case, determine its infestation prevalence, evaluate the hematological profile of cattle, and provide education program to farmers as well as implementing control program. Field surveillance was conducted by analyzing 40 fecal samples using native smear and sedimentation methods, along with blood examination using a hematology analyzer in cattle aged 3‒15 years. The results showed that 15 of 40 samples (37.5%) were positive for Fasciola spp. eggs, consisting of 7 positive samples by the native method, 5 by sedimentation method, and 3 by both methods. Hematological assay revealed a mean leukocyte count of 14.14 × 10⁹/L, slightly above the normal range, with granulocytes at 72.59%, hemoglobin at 90.38 g/L, and hematocrit at 33.19%, indicating an inflammatory response and a tendency toward mild anemia. These results suggest the presence of subclinical parasite infestation, which may contribute to reduced body weight and carcass quality, ultimately affecting farmers’ productivity and income. Treatment was administered following farmer education program and consent, consisting of oral anthelmintic suspension for therapeutic and preventive purposes, combined with intramuscular multivitamin injection to support recovery. This integrated approach underscores the importance of early detection, targeted treatment, and farmer awareness in controlling fascioliasis and sustaining livestock health.